The role of tolerance of ambiguity on ethical decision-making students: A comparative study between accounting and management students. Issue 3 (8th August 2016) - Moardi, Mahdi; Salehi, Mahdi; Marandi, Zakiyeh
Abstract : Purpose: This paper aims to investigate the role of affect and tolerance of ambiguity on ethical decision-making of management and accounting students. Design/methodology/approach: Weisbrod's (2009) questionnaire on ethical decision-making in individual and organizational situations, McDonald's (1970)16-factor questionnaire on tolerance of ambiguity and Watson et al. 's (1988) Positive and Negative Affect Schedule were used to study the students' views toward research hypotheses. The population used in this study includes graduate and PhD students of accounting and management during the academic year 2014-2015. The number of samples is 398 and sample members selected using simple random sampling method. Hypotheses test using structural equation modeling in the AMOS software version 18. Findings: Results of hypotheses shows that individual characteristics of positive and negative affect and tolerance of ambiguity have no effect on accounting students' ethical decision-making, but there is a significant positive relationship between management students' negative affect and ethical decision-making, and a significant negative relationship between management students' increased level of tolerance of ambiguity and ethical decision-making. The findings also show that affect (positive and negative) and tolerance of ambiguity have no interactive effect on accounting students' ethical decision-making, whereas among students of management, there is a significant relationship between interactive effect of negative affect and tolerance of ambiguity on ethical decision-making. The results show that there is a significant difference between students of management and accounting based on negative effects and tolerance of ambiguity on ethical decision-making. Originality/value: The current paper is almost the first paper which was conducted in developing countries.